1972
DOI: 10.1161/01.cir.46.4.666
|View full text |Cite
|
Sign up to set email alerts
|

Nonatheromatous Ischemic Heart Disease following Withdrawal from Chronic Industrial Nitroglycerin Exposure

Abstract: This report describes the clinical, angiographic, and hemodynamic findings in nine patients who manifested nonatheromatous' ischemic heart disease induced by chronic industrial exposure to nitroglycerin and subsequent withdrawal. They represent nearly 5% incidence in the group of 200 workers with similar exposure. One patient died suddenly, and the disease was commonly without premonitory symptoms. Of the eight survivors, five were studied and none showed evidence of significant organic obstructive disease. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
4

Year Published

1976
1976
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(54 citation statements)
references
References 7 publications
5
44
0
4
Order By: Relevance
“…Several features of the eight IHD deaths of workers who were under the age 45 years and actively exposed to nitroglycerin appear to be consistent with previous case reports of sudden death among workers following withdrawal from exposure to nitroglycerin and ethylene glycol dinitrate (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The workers in most previously reported cases were also under the age of 50 years and died suddenly without prior cardiovascular symptoms.…”
Section: Discussionsupporting
confidence: 85%
“…Several features of the eight IHD deaths of workers who were under the age 45 years and actively exposed to nitroglycerin appear to be consistent with previous case reports of sudden death among workers following withdrawal from exposure to nitroglycerin and ethylene glycol dinitrate (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The workers in most previously reported cases were also under the age of 50 years and died suddenly without prior cardiovascular symptoms.…”
Section: Discussionsupporting
confidence: 85%
“…One of these patients manifested the symptoms2 days after discontinuation of ISDN, and 2 patients developed coronary spasm. These results appear to be noteworthy in relation to the reports cited above (29,30).…”
Section: Discussionsupporting
confidence: 84%
“…Coronary vasospasm in the Nitrate group Lange et al (29) reported that coronary spasm occurred during nitrate-free intervals; this was based on the observation that when9 of 200 workers on vacation from a nitroglycerin explosive plant experienced myocardial ischemia, 5 of the workers did not exhibit atherosclerotic changes in coronary angiography. Experiments carried out in rabbits also demonstrated coronary spasm upon discontinuation of nitroglycerin (30).…”
Section: Discussionmentioning
confidence: 99%
“…Similar case reports have been published in other countries (264)(265)(266), and Morton's comprehensive review from 1977 (267) Half a year after Morton's review, Hogstedt & Axelson (271) introduced a new era in this research by publishing the first truly epidemiologic study. It was a case-referent study which was later supplemented with a prospective study (272) and with hygienic measurements (273), which together with two additional articles formed part of Hogstedt's thesis (274).…”
Section: Nitroglycerin and Ethylene Glycol Dinitrate (Nitroglycol)mentioning
confidence: 57%